Dynamics of an Anti-competitive Two Dimensional Rational System of Difference Equations
We investigate the global asymptotic behavior of solutions of the following anti-competitive system of rational difference equations equation* x_n+1=γ _1y_n A_1+x_n +h, y_n+1=β _2x_n A_2+y_n ,n=0,1,…, equation* where the parameters γ _1,β _2,A_1,A_2 and h are positive numbers and the initial conditions x_0,y_0 are arbitrary nonnegative numbers. 2000 Mathematics Subject Classification. 39A10, 39A11 , number=1, journal=Sarajevo Journal of Mathematics, author=Garić-Demirović, M. and Nurkanović, M., year=2024, month=Jun., pages=39–56